Cost-effectiveness of cemiplimab plus chemotherapy versus chemotherapy for the treatment of advanced non-small cell lung cancer - Liang, Xueyan; Chen, Xiaoyu; Li, Huijuan; Li, Yan (Frontiers in Oncology, 2023)
Background: In patients with advanced non-small cell lung cancer (aNSCLC), cemiplimab plus chemotherapy prolonged overall survival (OS) and progression-free survival (PFS) significantly compared to chemotherapy alone. The cost-effectiveness of these drugs is still uncertain. The aim of this study is to assess the cost-effectiveness of cemiplimab plus chemotherapy compared with chemotherapy for the treatment of aNSCLC from the third-party payer perspective in the United States. Materials and methods: The cost-effectiveness of cemiplimab with chemotherapy versus chemotherapy for the treatment of aNSCLC was evaluated using a partitioned survival model containing three mutually incompatible health states. The clinical characteristics and outcomes used in the model were gathered from EMPOWER-Lung 3 trial. We have conducted deterministic one-way sensitivity analysis and probabilistic sensitivity analysis in order to evaluate the robustness of the model. The primary outcomes considered were the costs, life-years, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefits (INHB), and incremental net monetary benefits (INMB). Results: Treatment of aNSCLC with cemiplimab plus chemotherapy increased efficacy by 0.237 QALYs and was associated with an increased total cost of $50,796 compared to chemotherapy alone, resulting in an ICER of $214,256/QALY gained. At a WTP threshold of $150,000/QALY, the INHB of cemiplimab plus chemotherapy was 0.203 QALYs and the INMB was $304,704 compared to chemotherapy alone. The probabilistic sensitivity analysis revealed that there was only a 0.04 percent chance that cemiplimab with chemotherapy would be cost-effective at a WTP threshold of $150,000/QALY. The performance of model was mainly determined by the price of cemiplimab, according to a one-way sensitivity analysis. Conclusions: From the third-party payer perspective, cemiplimab combined chemotherapy is unlikely to be a cost-effective option for the treatment of aNSCLC at the WTP threshold of $150,000/QALY in the United States.